Polysomnografic findings of obstrutive sleep apnea in children with adenotonsillar hypertrophy - Silva, Érico Campos Moreira [UNESP]; Moraes, Vinícius Rodrigues Silva de [UNESP]; Protetti, Helena; Weber, Silke Anna Theresa [UNESP] (Scientific Research Publishing, 2013)
Serous Background: There are few studies assessing the clinical manifestations of sleep breathing disorders and polysomnograms in several pediatric age ranges. This studied aimed to assess polysomnography results such as apnea-hypopnea index, mean oxygen saturation and sleep efficiency in children presenting with airway obstruction and adenotonsillar hypertrophy complaints, and to establish whether they are correlated to age and sex. Methods: A retrospective study with children of both sexes, aged between 2 and 12 years, with clinically suspected obstructive sleep apnea syndrome and adenotonsillar hypertrophy, who underwent polysomnography before surgery. The children were allocated to groups according to their age range (Group I: 2 to 4 years old; Group II: 5 to 8 years old; Group III: 9 to 12 years old). Apnea-hypopnea index, mean oxygen saturation and sleep efficiency data were compared between sexes and among the three groups (Student’s t test, p < 0.05). Results: Of 167 children studied by polysomnography, 76.6% were of school age and 67% were male. For all studied age ranges, there was no difference between sexes for the investigated parameters (body mass index, apnea-hypopnea index, mean oxygen saturation and sleep efficiency). As regards mean oxygen saturation, Group I showed the lowest value (89.9 ± 6.2). Apnea-hypopnea indexes were higher in male children aged between 2 and 4 years (9.9 ± 5.2). Group III had the lowest sleep efficiency (84.1 ± 9.2). Conclusion: There was a predilection of more severe cases of obstructive sleep apnea syndrome for children younger than four years, shown by higher apnea-hypopnea index per hour and lower mean oxygen saturation in this age range.
Keywords: Polysomnogram; Sleep architecture; Children; Obstructive sleep apnea; Sleep disordered breathing